2021
DOI: 10.3390/vaccines9040321
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvants and Vaccines Used in Allergen-Specific Immunotherapy Induce Neutrophil Extracellular Traps

Abstract: Aluminum hydroxide (alum) and monophosphoryl-lipid A (MPLA) are conventional adjuvants in vaccines for allergen-specific immunotherapy (AIT). Alum triggers the release of neutrophil extracellular traps (NETs) by neutrophils. NETs contain expelled decondensed chromatin associated with granular material and may act as danger-associated molecular patterns and activate antigen-presenting cells. We investigated whether adjuvant-induced NETs contribute to innate responses to AIT-vaccines. Human neutrophils were incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Contrarily to the OVA-induced model, the HDM-induced allergic model does not require aluminum hydroxide as an adjuvant and more closely resembles the heterogeneous nature of human allergic asthma. It is effectively well documented that alum, a conventional adjuvant that is approved for human vaccination for decades, can trigger the release of NETs by neutrophils [ 50 , 51 ], a feature that could obscure or even alter the effect of P140 peptide. The chronic HDM model is not only a more natural model that is closer to human pathophysiology, but is also free of this potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily to the OVA-induced model, the HDM-induced allergic model does not require aluminum hydroxide as an adjuvant and more closely resembles the heterogeneous nature of human allergic asthma. It is effectively well documented that alum, a conventional adjuvant that is approved for human vaccination for decades, can trigger the release of NETs by neutrophils [ 50 , 51 ], a feature that could obscure or even alter the effect of P140 peptide. The chronic HDM model is not only a more natural model that is closer to human pathophysiology, but is also free of this potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…An interval of 10 days between MPL injection and stress exposure abolished the preventive effect of MPL on CSDS-induced anxiety-like behaviors, which was rescued with consolidated immunization by a second MPL injection 10 days after the first MPL injection or 4 × MPL injections 1 day before stress exposure. As MPL is used as a vaccine adjuvant in clinic [ 35 , 36 ] and shows little toxicities compared to its parent molecule LPS [ 52 ], our findings may provide a promising alternative for the development of MPL as novel drugs for the prevention of anxiety-associated behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we selected MPL, a compound that possesses fewer undesirable actions and a significant therapeutic window compared to LPS [ 25 , 26 ], to study the preventive effect of innate immune pre-stimulation on chronic stress-induced anxiety-like behaviors. MPL is commercialized as a vaccine adjuvant [ 35 , 36 ] and can induce neuroprotective effects. Pre-administration of animals with a low dose of MPL has been demonstrated to protect the neurons against ischemic stimuli [ 37 ] and reduce seizure severity induced by traumatic brain injury or pilocarpine by reducing the over-production of pro-inflammatory cytokines in the brain [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data represent the mean ± SEM. We have previously demonstrated that sensitization to allergens, with a TLR4 or TLR9 agonist, prevents the development of Th2 lung inflammation without shifting the lung inflammation towards a Th1/Th17 pattern [1][2][3]. Classically, CpG-ODN signals through the MyD88 pathway [4], but at high CpG-ODN doses, the TRIF pathway could be involved [5].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The ovalbumin (OVA) allergen and the aluminum hydroxide gel (alum) adjuvant have been extensively used to induce Th2-cell-dominated immune responses in the lung [ 1 ]. In contrast, Toll-like receptor (TLR) agonists have been used as adjuvants to downmodulate the Th2-dominated immune response [ 1 , 2 ]. Among the TLR agonists used experimentally, a TLR4 agonist composed of monophosphoryl lipid A (MPLA), and a TLR9 agonist, composed of oligodeoxynucleotides (ODN) containing CpG motifs (CpG-ODN), have been extensively used in clinical trials [ 3 , 4 , 5 ] and a formulation with CpG-ODN has been approved for human use [ 6 ].…”
Section: Introductionmentioning
confidence: 99%